Efficacy, persistence and vector susceptibility to pirimiphos-methyl (Actellic® 300CS) insecticide for indoor residual spraying in Zanzibar. Issue 1 (December 2015) - Haji, Khamis; Thawer, Narjis; Khatib, Bakari; Mcha, Juma; Rashid, Abdallah; Ali, Abdullah; Jones, Christopher; Bagi, Judit; Magesa, Stephen; Ramsan, Mahdi; Garimo, Issa; Greer, George; et al.
Abstract Background Indoor residual spraying (IRS) of households with insecticide is a principal malaria vector control intervention in Zanzibar. In 2006, IRS using the pyrethroid lambda-cyhalothrine was introduced in Zanzibar. Following detection of pyrethroid resistance in 2010, an insecticide resistance management plan was proposed, and IRS using bendiocarb was started in 2011. In 2014, bendiocarb was replaced by pirimiphos methyl. This study investigated the residual efficacy of pirimiphos methyl (Actellic® 300CS) sprayed on common surfaces of human dwellings in Zanzibar. Methods The residual activity of Actellic 300CS was determined over 9 months through bioassay tests that measured the mortality of femaleAnopheles mosquitoes, exposed to sprayed surfaces under a WHO cone. The wall surfaces included; mud wall, oil or water painted walls, lime washed wall, un-plastered cement block wall and stone blocks. Insecticide susceptibility testing was done to investigate the resistance status of local malaria vectors against Actellic 300CS using WHO protocols; Anopheline species were identified using PCR methods. Results Baseline tests conducted one-day post-IRS revealed 100 % mortality on all sprayed surfaces. The residual efficacy of Actellic 300CS was maintained on all sprayed surfaces up to 8 months post-IRS. However, the bioassay test conducted 9 months post-IRS showed the 24 h mortality rate to be ≤80 % for lime wash, mud wall, water paint and stone block surfaces. Only oil paint surface retained the recommended residual efficacy beyond 9 months post-IRS, with mortality maintained at ≥97 %. Results of susceptibility tests showed that malaria vectors in Zanzibar were fully (100 %) susceptible to Actellic 300CS. The predominant mosquito vector species wasAn. arabiensis (76.0 %) in Pemba andAn. gambiae (83.5 %) in Unguja. Conclusion The microencapsulated formulation of pirimiphos methyl (Actellic 300CS) is a highly effective and appropriate insecticide for IRS use in Zanzibar as it showed a relatively prolonged residual activity compared to other products used for the same purpose. The insecticide extends the residual effect of IRS thereby making it possible to effectively protect communities with a single annual spray round reducing overall costs. The insecticide proved to be a useful alternative in insecticide resistance management plans.